2021
DOI: 10.5430/ijfr.v12n3p466
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Profitability and Firm Value: Evidence From Manufacturing Industry in Indonesia

Abstract: This study aims to test whether profitability acts as a moderating variable that is able to moderate the influence of the company growth and capital structure on the firm value. The independent variables used in this study are company growth and capital structure, while profitability is the moderating variable.The research sample was taken from manufacturing industrial companies listed on the Indonesia Stock Exchange (IDX) during the period 2016 - 2018. The study used panel data which is a combination of cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
7
0
3
Order By: Relevance
“…The level of revenue growth (FGrowth) has a negative effect on the value of the firm. In contrast with this research, Sudiyatno et al (2021) [50] stated that in companies with strong profitability, firm growth will decrease firm value. Financial leverage (LEV) is defined as total debt divided by total assets.…”
Section: Resultsmentioning
confidence: 72%
“…The level of revenue growth (FGrowth) has a negative effect on the value of the firm. In contrast with this research, Sudiyatno et al (2021) [50] stated that in companies with strong profitability, firm growth will decrease firm value. Financial leverage (LEV) is defined as total debt divided by total assets.…”
Section: Resultsmentioning
confidence: 72%
“…The corporate financial performance is the core value of the company's business activities. Sudiyatno et al (2012) found that there is an effect of financial performance on firm value in Indonesia. Improved financial performance is a good signal for market participants, thereby increasing the company's value.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Dalam hal ini, manajemen yang telah mendapatkan kepercayaan dari pemilik berusaha untuk bekerja keras untuk mencapai tujuan ini. Manajemen akan menjalankan bisnis dengan mengelola aset perusahaan secara efektif agar mampu menghasilkan nilai tambah bagi perusahaan, termasuk dalam pengambilan keputusan strategis (Sudiyatno et al, 2021). Tujuan utama perusahaan adalah untuk meningkatkan kesejahteraan pemilik atau nilai perusahaan dengan memaksimalkan harga pasar saham perusahaan.…”
Section: Pendahuluanunclassified